02.31 Targeted inhibition of macrophage inflammatory protein 1-alpha (ccl3) prevents pit formation by human osteoclasts and potently attenuates the erosion of bone in collagen-induced arthritis. (1st March 2017) - Jordan, Lauren A; Fenner, Benjamin F; Davies, Ruth; Harvey, Ann K; Choy, Ernest H; Errington, Rachel; Bokarewa, Maria; Williams, Anwen S
Abstract : Background: In patients with rheumatoid arthritis (RA), osteolysis, osteopenia and osteoporosis are predictive of a severe disease phenotype. CCL3 is a chemokine associated with inflammatory osteolytic lesions and bone resorption by osteoclasts in patients with multiple myeloma. CCL3's role in modulating bone destruction during inflammatory arthritis has not been established. The purpose of this study was to assess pharmacological blockade of CCL3 as a strategy to prevent or inhibit osteoclast-associated bone damage during inflammatory arthritis. Method: Fully differentiated osteoclasts were formed from human CD14-positive mononuclear cell precursors cultured with macrophage-colony stimulating factor (m-CSF) and receptor activator of nuclear factor kappa-B ligand (RANKL). Collagen-induced arthritis (CIA) was selected for in vivo studies. Antibodies (anti-CCL3 and isotype control) were tested for their potency to modulate; (i) osteoclast differentiation and resorption of bone substrate in vitro and (ii) arthritis severity, synovial inflammation by histology and bone erosion by x-ray. Results: The concentration of CCL3 in supernatants increased in a time-dependent manner over the 14-day osteoclast culture period (p<0.05). There was a strong, specific correlation between osteoclast number and CCL3 level (p<0.01). Significant concentration-dependent inhibition of osteoclastogenesis was observed by neutralising CCL3 (p≤0.05). The erosion of ivory discs by osteoclasts was reduced significantly (p≤0.05) by ant-CCL3. Mean area of disc resorbed was 0.2% (anti-CCL3), 0.1% (osteoprotegerin) and 1.5% (Isotype control). Synovial inflammation and joint erosion by histology were both significantly reduced by CCL3 blockade in CIA. The composite histology score was 3.8±0.36 (anti-CCL3) versus 6.8±0.6 (isotype control). Osteoclast number was significantly reduced in the wrist (p<0.05) and elbow (p<0.05) joints by anti-CCL3 blockade. Bone erosion by x-ray in the hind paws (p<0.05) and fore paws (p<0.01) was also significantly reduced by anti-CCL3. Conclusion: Targeted inhibition of CCL3 protect the synovial joint against arthritis-associated pathology by potent inhibition osteoclast formation and bone erosion. Our data may help guide future innovations for the diagnosis and treatment of inflammatory arthritis.